2001
DOI: 10.1111/j.1469-7793.2001.00447.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of hypoglossal motoneuron excitability by NK1 receptor activation in neonatal mice in vitro

Abstract: The effects of substance P (SP), acting at NK1 receptors, on the excitability and inspiratory activity of hypoglossal (XII) motoneurons (MNs) were investigated using rhythmically active medullary‐slice preparations from neonatal mice (postnatal day 0‐3). Local application of the NK1 agonist [SAR9,Met (O2)11]‐SP (SPNK1) produced a dose‐dependent, spantide‐ (a non‐specific NK receptor antagonist) and GR82334‐(an NK1 antagonist) sensitive increase in inspiratory burst amplitude recorded from XII nerves. Under cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 81 publications
4
19
0
Order By: Relevance
“…Previous reports have shown that SP depolarizes respiratory neurons (Gray et al, 1999;Shvarev et al, 2002Shvarev et al, , 2003 and respiratory-related phrenic and hypoglossal motoneurons (Ptak et al, 1999(Ptak et al, , 2000Yasuda et al, 2001). Here, we demonstrate that this depolarization was not specific to a subpopulation of inspiratory PBC neurons.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Previous reports have shown that SP depolarizes respiratory neurons (Gray et al, 1999;Shvarev et al, 2002Shvarev et al, , 2003 and respiratory-related phrenic and hypoglossal motoneurons (Ptak et al, 1999(Ptak et al, , 2000Yasuda et al, 2001). Here, we demonstrate that this depolarization was not specific to a subpopulation of inspiratory PBC neurons.…”
Section: Discussionsupporting
confidence: 49%
“…SP activates voltage-dependent Ca 2ϩ channels, voltage-dependent K ϩ conductances, Cl Ϫ currents, Ih currents, voltage-dependent Na ϩ channels, and nonselective cationic channels (Adams et al, 1983;Stanfield et al, 1985;Bley and Tsien, 1990;Shen and North, 1992;Bertrand and Galligan, 1994;Aosaki and Kawaguchi, 1996). In most neurons, SP depolarizes membrane potential by decreasing resting K ϩ conductances (Akasu et al, 1996;Lepre et al, 1996;Ptak et al, 2000;Yasuda et al, 2001). This seems not to be the case for respiratory neurons because the slow depolarization persisted after blocking K ϩ channels with TEA externally or cesium internally.…”
Section: Discussionmentioning
confidence: 99%
“…In neonatal lumbar motoneurons, the substance P-evoked depolarization was attributable to the suppression of a Ba ϩ -sensitive K ϩ conductance (Fisher and Nistri, 1993). In phrenic motoneurons and in hypoglossal motoneurons, NK1 receptor activation induced membrane depolarization, or evoked an inward current, by inhibiting a resting K ϩ current (Ptak et al, 2000;Yasuda et al, 2001). In hypoglossal motoneurons, this excitatory effect was at least in part mediated by the two-pore domain K ϩ channel TASK-1 (TWIK-related acid-sensitive K ϩ channels) (Talley et al, 2000).…”
Section: Mechanism Of Action Of Vasopressinmentioning
confidence: 99%
“…In contrast, NK2 and NK3 receptor agonists were ineffective in eliciting any direct response. It has been reported by others that tachykinins can induce depolarization or generate an inward current in nonpudendal spinal motoneurons or in brainstem motoneurons (Konishi and Otsuka, 1974;Otsuka and Yanagisawa, 1980;Fisher and Nistri, 1993;Fisher et al, 1994;Ptak et al, 2000;Yasuda et al, 2001).…”
Section: Comparison With Nonpudendal Motoneuronsmentioning
confidence: 99%
“…SP increases excitability through the closure of K ϩ channels in hypoglossal motoneurons (Yasuda et al 2001) and C1 neurons that are situated at the ventral border of the preBötC (Blessing 1997;Li and Guyenet 1997). Our data set did not contain C1 neurons because I SP never reversed at E K and was unaffected by intracellular and extracellular K ϩ channel blockers.…”
Section: Biophysics Of I Sp In Inspiratory Neuronsmentioning
confidence: 99%